Preeclampsia Prevalence and Fetal Outcome over 5 Years Review – A Single Centre Experience - Nur Zaireena Zainal; Nur Fariha Mohd Manzor; Noor Fadzilah Zulkifli; Marjanu Hikmah Elias; Hayati Abd Rahman; Lim Kar Koong (John Wiley & Sons Ltd on behalf of International, 2024)
International Journal of Gynecology & ObstetricsVolume 155, Issue S2 p. 127-532